Blockchain Technology as a Catalyst for Transforming Property Title Documentation and Land Records in Nigeria: A Conceptual Assessment - Nwosu, C. C.; Okoro, A. C. (International Journal of Real Estate, 2026)
Background: Nigeria's land administration system is plagued by inefficiencies, fraud, corruption, bureaucratic bottlenecks, and poor documentation, which collectively undermine property rights, discourage investment, and lock vast land resources as "dead capital." The Land Use Act of 1978, while intended to unify land tenure, has created additional complications in title registration and documentation across the country. This study assesses the potential of blockchain technology as a transformative tool for property title documentation and land records management in Nigeria.This conceptual study employs a systematic review of literature, comparative analysis of blockchain pilot projects in Sub-Saharan Africa, mathematical statistical analysis of land registry data, and a framework design approach to evaluate the applicability of blockchain technology to Nigeria's land administration context. The study identifies critical weaknesses in Nigeria's current land records system, including high costs of registration (15% of property value 4.5x the global comparator average), lengthy processing times (mean: 330 days, SD: 418 days), corruption (mean score: 70.4%), and low registration rates (0.128% of estimated total parcels). Blockchain technology offers solutions through decentralization, immutability, transparency, and smart contract automation, with global evidence showing 80-95% improvement across key metrics. However, significant challenges remain, including legal uncertainties, high implementation costs, digital literacy gaps, and institutional resistance. Blockchain technology presents a viable pathway for transforming Nigeria's land records system, with a projected break-even point at Year 4 and 10-year net benefit of $570 million. Successful implementation requires concurrent legal reforms, infrastructure development, stakeholder capacity building, and a phased pilot approach before nationwide rollout.
Keywords: Blockchain; Land Registry; Property Title; Land Administration; Nigeria; Land Use Act; Digital Transformation; Smart Contracts; Statistical Analysis